PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK DIGITAL BERBASIS KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK - Aelfi Situmorang; Glory Indira Diana Purba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to (1) determine the quality of context-based digital worksheets in improving students’ mathematical communication skills; (2) examine the response process of students with mathematical communication skills who learn using a contextual model; (3) determine the improvement in students’ mathematical communication skills through contextual learning using the developed digital worksheets. The research method used in this study is the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were 11th-grade students in the English and Biology class at SMA Negeri 1 Percut Sei Tuan, and the research object was the context-based digital worksheet designed to improve students’ mathematical communication skills. The instruments used in this study were questionnaires and tests. The results of the study indicate that: (1) The quality of the context-based digital worksheets developed to improve students’ mathematical communication skills on the topic of functions has met the criteria for validity, practicality, and effectiveness. The developed digital worksheets received a score of 3.96 from the content expert and 3.8 from the media expert; both scores fall within the range of 3.4 < V ≤ 4.2, so both are categorized as valid. The digital worksheets developed scored 92.63% for teacher practicality and 88.8% for student practicality; both scores fall within the range (80 < Vp ≤ 100), so both are categorized as highly practical; The developed digital worksheets met the criteria for effectiveness based on (a) student learning mastery, with 26 students achieving mastery or a score of 75 and a class-wide learning mastery rate of 86.66%; (b) the achievement of individual learning indicators/objectives at 78.44%; (c) positive responses from students at 92.67% in the positive category. (2) An increase in mathematical communication skills from an average pretest score of 26.39 to 63.39 on the posttest. Communication ability indicators also increased: the first indicator rose by 59.72%, the second by 42.5%, and the third by 49.17%. N-Gain analysis showed an increase of 0.71, which is categorized as high.